Development of a Resistive Plate Chamber with heat strengthened glass. (29th September 2016) - Majumder, G.; Datar, V.M.; Kalmani, S.D.; Mondal, N.K.; Mondal, S.; Satyanarayana, B.; Shinde, R.R.
Abstract: The INO-ICAL is a proposed neutrino physics experiment, in which RPCs will be used as active detectors. The Iron Calorimeter (ICAL) detector will be made of 50 kTon of low carbon magnetized steel layers, tiled with 4 m × 2 m × 56 mm thick plates, alternating with layers of RPCs. The total number of 2 × 2 m 2 RPCs required will be about 29000. However, during the assembly of RPCs, handling the 2 × 2 m 2 normal float glass of thickness 3 mm is both difficult and risky. This prompted us to make RPCs with toughened glass and to characterize them. Toughened and tempered glass have higher mechanical strength compared to normal float glass and their processing involves controlled thermal or chemical treatment during the industrial production. This paper presents a comparison of the characteristics, such as noise rate, dark current, particle detection efficiency and time resolution, of normal and hardened glass RPCs.